2022
DOI: 10.3389/fmolb.2022.783735
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of the Developmental Gene FZD6 in Young Saudi Breast Cancer Patients: A Biomarkers Discovery and Cancer Inducers OncoScreen Approach

Abstract: Wnt signalling receptors, Frizzleds (FZDs), play a pivotal role in many cellular events during embryonic development and cancer. Female breast cancer (BC) is currently the worldwide leading incident cancer type that cause 1 in 6 cancer-related death. FZD receptors expression in cancer was shown to be associated with tumour development and patient outcomes including recurrence and survival. FZD6 received little attention for its role in BC and hence we analysed its expression pattern in a Saudi BC cohort to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“…All accepted articles were divided into 3 categories. The results published in the first category of the RT supported the notion of previous reports showing that many genes function in a dual role manner in development and disease ( Gong et al, 2011 ; Teven et al, 2014 ; Sohn et al, 2016 ; Stepicheva and Song, 2016 ; Mahajan et al, 2021 ; McMillen et al, 2021 ; Assidi et al, 2022 ). Other reports showed that during development components of the FGF, Wnt, Notch, BPM, and Hedgehog signaling orchestrate crucial cellular events including proliferation, migration, differentiation, epithelial-mesenchymal transition (EMT), morphogenesis and somite myogenesis patterning.…”
Section: Discussionsupporting
confidence: 87%
“…All accepted articles were divided into 3 categories. The results published in the first category of the RT supported the notion of previous reports showing that many genes function in a dual role manner in development and disease ( Gong et al, 2011 ; Teven et al, 2014 ; Sohn et al, 2016 ; Stepicheva and Song, 2016 ; Mahajan et al, 2021 ; McMillen et al, 2021 ; Assidi et al, 2022 ). Other reports showed that during development components of the FGF, Wnt, Notch, BPM, and Hedgehog signaling orchestrate crucial cellular events including proliferation, migration, differentiation, epithelial-mesenchymal transition (EMT), morphogenesis and somite myogenesis patterning.…”
Section: Discussionsupporting
confidence: 87%
“…In conjunction to the miRNA prediction analysis carried out in the present study, the expression of another WNT receptor (FZD6) in BC was previously analyzed by the authors ( 74 ). It was demonstrated that the FZD6 prognostic value was more potent in younger patients with BC, which indeed is not the case for FZD8 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, at least 18 miRNAs were predicted to silence FZD6 expression, presented with a high prediction score. Specifically, the miRNAs were hsa-miR-101-3p, hsa-miR-302b-3p, hsa-miR-302d-3p, hsa-miR-372-3p, hsa-miR-373-3p, hsa-miR-520c-3p, hsa-miR-519a-3p, hsa-m i R-519b -3p, hsa-m i R-568, hsa-m i R-545 -3p, hsa-miR-130a-3p, hsa-miR-130b-3p, hsa-miR-301a-3p, hsa-miR-301b-3p, hsa-miR-454-3p, hsa-miR-3121-3p, hsa-miR-19a-3p, and hsa-miR-19b-3p (74). In this previous study by the authors, the predicted miRNAs that could target FZD6 expression were compared with those predicted to target FZD8 expression in BC.…”
Section: Fzd8 Protein Expression Pattern (%) -mentioning
confidence: 99%
“…FZD6, a member of the frizzled family, is a receptor for Wnts. There are numerous studies show that FZD6 expression is associated with the malignancy and prognosis of breast cancer, cervical cancer and human glioblastoma ( Zhang et al, 2021b ; Wang et al, 2021 ; Assidi et al, 2022 ). FZD6 also can inhibit the migration and proliferation of gastric cancer cells via targeting miR-21 to activate the non-classical Wnt pathway ( Yan et al, 2016 ; Ko et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%